Réponses

2013-04-13T18:07:43+02:00

 25y²-49-(5y+7)(2y+6)=0

(5y +7) ( 5y -7) - ( 5y +7 )( 2y +6 ) = 0

( 5y +7 ) ( 5y -7 -2y -6 ) = 0

( 5y +7 ) ( 3y -13 ) = 0

 

5y +7 = 0                 3y -13 = 0

5y = -7                       3y = 13

y = -7 /5                     y = 13 /3

Cette équation admet 2 solutions, x = -7 / 5 et x = 13 / 3

  • Utilisateur Brainly
2013-04-13T18:14:50+02:00

Alor moi j'ai trouvé sa un peu comme cathy :

 

5y +7 = 0                 3y -13 = 0

5y = -7                       3y = 13

y = -7 /5                     y = 13 /3